Rediscovery of the Endangered frog Phrynopus montium (Shreve, 1938) Amphibia, Anura, Craugastoridae) in the cloud forest of central Peru - May, Rudolf Von (Zootaxa, 2017)
Phrynopus montium (Shreve, 1938) was described from Cascas, Junín Department, Peru, at an undetermined elevation between 3000 and 4000 m a.s.l. in the Cordillera Central. With the exception of the type specimens used in the original description, no additional sightings of P. montium had been reported for 76 years. Additionally, its coloration in life, microhabitat use, and precise elevational distribution remained unknown. During a field expedition conducted in 2014, two individuals of P. montium were found at an upper cloud forest site in central Peru, 8.7 km south from Hacienda Cascas. Here, I describe the coloration in life, microhabitat use, and elevation of these individuals.